Influence of Protection Layers on Thermal Stability of Nitride Thin Films. Issue 8 (26th June 2021) - Zakutayev, Andriy; Perkins, Craig L.
Abstract : Nitrides are commonly studied for their properties relevant to numerous coating applications, and have been recently used to synthesize newly predicted materials in thin‐film form. However, the thermodynamic stability of such nitride materials is difficult to experimentally evaluate, due to the limited thermal budget of thin films. Herein, it is shown that the thermal stability of nitride films can be extended using protection layers. Specifically, it is found that zirconium nitride (ZrN) thin films are stable up to at least 1200 °C annealing temperature in N2 atmosphere, if aluminum nitride (AlN) diffusion barriers and capping layers are used. X‐ray diffraction (XRD) measurements show the expected thermodynamically stable rocksalt structure of ZrN, and scanning electron microscopy (SEM) confirms the compact microstructure of these ZrN films. Without such protection layers, the transient bixbyite Zr2 ON2 phase and high‐temperature ZrSi2 phase are observed after annealing by XRD, SEM, and Auger electron spectroscopy (AES), due to side reaction with the native surface oxide (ZrO x ) and the substrate (Si), respectively. These results demonstrate that protection layers are beneficial to increase the thermal budget of nitride thin films, for evaluating rgw thermodynamic stability of new nitride materials, for capturing transient metastable phases during crystallization, and for using functional nitride coatings in extreme environments. Abstract : Protective aluminum nitride coatings, such as diffusion barriers and capping layers, extend the thermal stability of zirconium nitride thin films up to 1200 °C in a nitrogen atmosphere. Such protective layers can be used to extend the operating temperature of functional nitride coatings, evaluate the thermodynamic stability of nitrides in thin‐film form, and capture transient metastable phases of new nitride materials.